2020
DOI: 10.1177/0363546520944147
|View full text |Cite
|
Sign up to set email alerts
|

An Iliopsoas Impingement Lesion in the Absence of Painful Internal Snapping May Not Require Iliopsoas Fractional Lengthening

Abstract: Background: Iliopsoas impingement (IPI) has been associated with a distinct lesion on the anterior labrum. Iliopsoas fractional lengthening (IFL) can treat IPI in instances of painful internal snapping (PIS) and mechanical groin pain. Purpose: To report minimum 2-year outcomes of patients without PIS who had an IPI lesion diagnosed intraoperatively that did not undergo IFL (+IPI –PIS –IFL) as compared with a matched group of patients with PIS and an IPI lesion that was treated with IFL (+IPI +PIS +IFL). Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…(2021) and Meghpara et al . (2020) have highlighted the importance of careful patient selection and judicious use of IFL [ 4 , 10 ]. Matsuda et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021) and Meghpara et al . (2020) have highlighted the importance of careful patient selection and judicious use of IFL [ 4 , 10 ]. Matsuda et al .…”
Section: Resultsmentioning
confidence: 99%
“…Meghpara et al . found that IFL did not significantly improve PRO for patients without painful internal snapping, further emphasizing the need for careful patient selection and consideration of alternative treatment options [ 4 ]. Thus, iliopsoas tenotomy and IFL should not be routinely used without clear internal snapping hip pathology present pre-operatively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been our experience that an iliopsoas impingement lesion in the absence of painful internal snapping does not require IFL. 6 Although performing an IFL using the transbursal approach is feasible, in our experience, there are key technical pearls to diminish the risk of complications and obtain favorable outcomes. 8 In the setting of FAIS and labral tear, labral restoration and accurate bony morphology correction are important.…”
mentioning
confidence: 81%
“…1 It is a cautionary tale that certain studies have demonstrated early postoperative weakness and iliopsoas atrophy on radiological imaging. Furthermore, the data in outcomes after hip arthroscopy in patients with painful snapping without IFL are scarce, 6 which makes the current study presented by Matsuda et al 3 very valuable. The first line for the treatment of iliopsoas pathology should be conservative treatment.…”
mentioning
confidence: 98%